(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
This paper focuses on Reusability. Reusability is one of the most significant software quality indicator its correct quantification directs to the prospects of facilitating as well as improving software maintenance process. Reusability is strongly related to maintainability and constantly plays a key role to deliver high class maintainable and trustworthy software within time and budget. In this paper an endeavor has been made to establish a correlation between object oriented design constructs and Reusability. A Reusability Quantification Model (RQMOOD) has been proposed for Object Oriented Design by using multiple linear regression. Finally, the proposed model has been validated using experimental tryout.